AN INSIGHT INTO ENDOMETRIOSIS: ROLE AND INFLUENCE OF THE PROCESS OF ANGIOGENESISS - Nikolai Lazarov; Faisal Saghir (Peytchinski Publishing, 2024)
Introduction: Endometriosis is one of the most common gynaecological disorders present in females. According to the implantation of ectopic endometrial tissue outside of the uterine cavity, angiogenesis is an essential prerequisite for the progression of the disease. The purpose is to provide insight and a better understanding of the role that angiogenetic factors play within endometriosis and how this can translate into more effective diagnostic and therapeutic approaches taken by medical specialists when treating this disease. Materials and methods: We conducted a review of the available scientific literature on PubMed, Google Scholar and Science Direct, which included randomized controlled trials, observational studies, prospective controlled studies and case reports. Results and Discussion: Our review of the scientific literature showed that the role of angiogenesis upon the development of endometrial ectopic tissue is very significant, and a positive relationship is established with an increase in neo-angiogenesis and a quicker rate of development of ectopic endometrial tissue. We also found data indicating that there are a multitude of angiogenetic and anti-angiogenetic factors functioning in a homeostatic manner to provide an optimal environment for the endometrial tissue to proliferate and for translocation for the implantation of the ectopic tissue within different locations both within the uterine cavity and distant anatomical locations and regions located outside of the uterine cavity. Conclusion: Recently, the research surrounding the process of angiogenesis is positive and positive correlations have been established between the role of angiogenesis and the extent to which the ectopic endometrial tissue proliferates.